2004
DOI: 10.1007/s00330-004-2310-8
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of spinal infection: atypical features, interpretative pitfalls and potential mimickers

Abstract: The wide variability of MR features in spinal infection reflects rare distribution of discovertebral involvement, unexpected soft-tissue and bone abnormalities, un-usual complications or uncommon pathogens. In addition, several de-generative and inflammatory entities can clinically and radiologically resemble spinal infection. In this pictorial review, we illustrate the various atypical features that may be found in MR imaging of spinal infection,with emphasis on interpretative pit-falls and common mimickers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 31 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Characteristic imaging findings and isolation of the causative organism are the main tools for the correct diagnosis [1]. Plain radiographs, computed tomography (CT), scintigraphic techniques, and magnetic resonance imaging (MRI) can all be used in the diagnosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic imaging findings and isolation of the causative organism are the main tools for the correct diagnosis [1]. Plain radiographs, computed tomography (CT), scintigraphic techniques, and magnetic resonance imaging (MRI) can all be used in the diagnosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] This is another important route of infection resulting in epidural/ paraspinal abscesses. Facet joint infection is often haematogenous but also caused by epidural anaesthesia and spinal procedures.…”
Section: Epidural/paraspinal Abscess With Facet Joint Infectionmentioning
confidence: 99%
“…The reticulated porous lesions found on the vertebral neural arches could also be evoked as a possible feature for disease discrimination. Destruction on the posterior vertebral elements, through extension of the vertebral body infection, may occur in both pathological processes (Jevtic, 2004;Harada et al, 2008), but the involvement of the pedicle, laminae and spinous process has been reported to occur more often in spinal tuberculosis and less encountered in pyogenic infection (Magnus & Hoffman, 2000;Jinkins, 2002;Mellado et al, 2004;Quiñ ones-Honojosa et al, 2004;Turunc et al, 2007;Harada et al, 2008). The neural arches affection in clinical surveys were observed in 5%, 40% and 61,5% of tuberculous spondylitis patients, respectively by Kumar (1985in Weber et al, 2004, Magnus & Hoffman (2000) and Turunc et al (2007).…”
Section: Infectious Conditionsmentioning
confidence: 99%
“…This has long been pointed out that it has a source of distinction from pyogenic spondylitis. But it must be emphasised that recent clinical studies (Ledermann et al, 2003;Mellado et al, 2004) demonstrated that patients with non-tuberculous bacterial infections presented also 'frank vertebral collapse with resulting gibbus deformity' (Ledermann et al, 2003: p. 513). These studies, along with those above quoted for fungal infections illustrate the need for extreme caution when considering gibbus deformity as the epitome of tuberculosis.…”
Section: Infectious Conditionsmentioning
confidence: 99%